PROBLEMS OF FEMALE CRIMINAL BEHAVIOR - Michailovič, Ilona (Teisė, 2015)
The problem of female criminal behavior, in comparison to the male criminality, is rarely the object of theoretical and empirical research. Although females make more than a half of all adult world population, they commit crimes almost ten times less frequently. Scientists have tried many times to find out and firstly to understand the motivation of female culprit activities. Official statistics reflect both changes in criminal behavior and law enforcement policy changes. For instance, more women in the police can affect the equal treatment of women. The attitude that criminal behavior is exceptionally typical of males is increasingly disappearing. It must be emphasized that there is a tendency in contemporary criminology, the essentiality of which is wider contemplation on the causality of criminal behavior, and the continuation of this tendency seems correct in order to acknowledge deviational behavior etiology. It would therefore be appropriate either to develop separate women’s and men’s theories of criminal behavior or to supplement the general theories in the light of gender perspective. It is also important to pay more attention to the younger age groups – girls’ behavioral research.